KEARIFAN LOKAL DALAM PENGELOLAAN KERBAU MOA PADA MASYARAKAT PULAU MOA PROVINSI MALUKU - Tatipikalawan, Jomima Martha; Sangadji, Insun (JURNAL HUTAN PULAU-PULAU KECIL, 2024)
The purpose of this study is a study of the application of local wisdom in the management of Moa buffalo. This research was conducted on Moa Island, Southwest Maluku Regency, Maluku Province. The research used survey method. The data collected consists of primary and secondary data. Primary data collection was carried out using FGD techniques and observations involving farmers, traditional stakeholders, saniri, soa heads, village heads, government representatives. Secondary data are obtained through the results of previous research and related agencies. Data is analyzed descriptively through several stages, namely surveys, research implementation, data analysis, discussion and conclusions. The results showed that until now local wisdom practices in the management of Moa buffalo that are passed down from generation to generation still exist which include the division of shepherd groups in East Moa based on soa or clan system and the use of buffalo as a tool of customary sanctions. The use of buffalo for traditional ceremonies is not judged based on the selling price but is determined based on body weight and amount in accordance with applicable customary rules. Moa buffalo is also used for dowry, house cover, medium of exchange (buying land and motor vehicles), marking on livestock (ear tags), grazing systems and housing (lutur). The use of buffalo for traditional death ceremonies is no longer used because it is considered burdensome for bereaved families.